Prevalence of neuropathic pain and factors affecting sleep quality in women with breast cancer after radiotherapy - Mehdi Khanbabaei Gol; Forough Rezvani; Zahra Ghavami; Noushin Mobaraki-Asl (Mashhad University of Medical Sciences, 2019)
Introduction: Neuropathic pain can be one of the main causes of decreased sleep quality, and undesirable sleep quality has negative effects on quality of life and treatment continuation. This study was performed with aim to evaluate neuropathic pain and factors affecting sleep quality in women with breast cancer after radiotherapy. Methods: This descriptive-correlational study was performed from 21March 2017 to 20February 2019 on women with breast cancer undergoing radiotherapy in Imam Reza Educational Center, Tabriz University of Medical Sciences. The tools included demographic characteristics, VAS pain questionnaire, and Pittsburgh Sleep Disorders Questionnaire which measured neuropathic pain and sleep status. Data was analyzed by SPSS software (version 20) and multivariate regression test. P <0.05 was considered statistically significant. Results: Mean of pain severity in patients participating in the study was 06.55±1.03 and mean score of sleep was 12.29±3.20. According to regression results, the variables of age (P=0.012), pain intensity (P=0.001), mastectomy (P=0.011), lymph nodes removal (P=0.03), number of radiotherapy sessions (P=0.003), history of chemotherapy (P=0.002) and stage of disease (P=0.01) significantly predicted sleep disorder. Conclusion: Prevalence of neuropathic pain after radiotherapy in women with breast cancer was high in this study, and this pain was the predictor of sleep disorder in these women.